The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s11356-016-7258-0
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of health impacts and external costs of natural gas-fired power plant of Qom

Abstract: The external health damage costs of the combined cycle natural gas-fired power plant of Qom were investigated via the simplified impact pathway approach. Emitted particulate matter (PM) and gaseous pollutants (NO , CO, and SO) from the power plant stack were measured The health effects and related costs were estimated by QUERI model from AirPacts according to the emissions, source and stack parameters, pollutant depletion velocities, exposure-response functions, local and regional population density, and detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…O período considerado inicia-se em 2004, devido à disponibilidade dos dados sobre emissão, até 2018. O Simplified Approach of Estimating Impacts of Electricity Generation (SIMPACTS) (IAEA, 2020) utiliza os dados demográficos e técnicos da usina para poder quantificar os danos à saúde ao redor da UTE de carvão mineral devido à atividade de geração de energia elétrica, trabalhos similares foram realizados em outros países usando o SIMPACTS (Hainoun et al, 2010;Nwanya, 2011;Fard et al, 2016;Jorli et al, 2017), no Brasil existem estudos similares em relação aos impactos ambientais causados pela poluição de termelétricas (Hoffmann, 2013;Almeida et al, 2019;Pedruzzi et al, 2019). A UTE a carvão mineral encontra-se instalada no Município de Figueira, no Estado do Paraná, sul do Brasil, que, de acordo com o IBGE (2010) possui uma área de 129,769 km², com população de 8.293 habitantes e densidade demográfica de 63,91 hab/km².…”
Section: Metodologiaunclassified
“…O período considerado inicia-se em 2004, devido à disponibilidade dos dados sobre emissão, até 2018. O Simplified Approach of Estimating Impacts of Electricity Generation (SIMPACTS) (IAEA, 2020) utiliza os dados demográficos e técnicos da usina para poder quantificar os danos à saúde ao redor da UTE de carvão mineral devido à atividade de geração de energia elétrica, trabalhos similares foram realizados em outros países usando o SIMPACTS (Hainoun et al, 2010;Nwanya, 2011;Fard et al, 2016;Jorli et al, 2017), no Brasil existem estudos similares em relação aos impactos ambientais causados pela poluição de termelétricas (Hoffmann, 2013;Almeida et al, 2019;Pedruzzi et al, 2019). A UTE a carvão mineral encontra-se instalada no Município de Figueira, no Estado do Paraná, sul do Brasil, que, de acordo com o IBGE (2010) possui uma área de 129,769 km², com população de 8.293 habitantes e densidade demográfica de 63,91 hab/km².…”
Section: Metodologiaunclassified
“…Also, it was shown that using renewable energies instead of fossil fuel reduced15-20% of external costs during nine years (El-Guindy and Mahmoud, 2014). The assessment of health impacts and external costs of a natural gas power plant in Iran was also performed using the ExternE method (Fouladi Fard et al, 2016). The annual external cost of emission for selected gas power plant with 714 MW generation capacity was approximately 4.76 million US$.…”
Section: Introductionmentioning
confidence: 99%